Efficacy of Biologics Targeting Tumour Necrosis Factor-alpha, Interleukin-17 -12/23, -23 and Small Molecules Targeting JAK and PDE4 in the Treatment of Nail Psoriasis: A Network Meta-analysis - Júlia Szebényi; Noémi Gede; Péter Hegyi; Zsolt Szakács; Margit Solymár; Bálint Erőss; András Garami; Kornélia Farkas; Dezső Csupor; Rolland Gyulai (Medical Journals Sweden, 2020)
The comparative efficacy of registered anti-psoriatic biologics and small molecules in treating nail symptoms has not been systematically evaluated. The aim of this study was to perform a network meta-analysis to determine the efficacy of biologics and small molecules in nail psoriasis. A Bayesian network meta- analysis of 17 randomized clinical trials (a total of 6,053 nail psoriatic patients) was performed, comparing the short-term (week 10-16) efficacy of biologics and small molecules in the treatment of nail psoriasis. All active treatments were found to be superior to placebo. Ixekizumab 80 mg every 4 weeks (Nail Psoriasis Severity Index (NAPSI) % improvement, Surface Under the Cumulative Ranking (SUCRA)=0.92) and etanercept 50 mg twice weekly (probability of achieving NAPSI 50, SUCRA=0.82) proved the best short-term treatment options. However, efficacy end-points in psoriasis trials were not optimized for nail assessment, and outcome parameters were highly heterogeneous, limiting comparability. In conclusion, outcome parameters and efficacy endpoints of nail psoriasis trials should be standardized.